PROBLEMATIKA PELAKSANAAN PEMBELAJARAN TEMATIK PADA SDN GUGUS 7 KECAMATAN PUJUT TAHUN AJARAN 2019/2020 - Rahimayatul Aini; Ida Ermiana; Lalu Hamdian Affandi (Renjana Pendidikan Dasar, 2022)
The problem of implementing learning at SDN Cluster 7, Pujut District is very complex. Some of the problems that occurred were: difficulties in the assessment process; limited creativity of teachers; the use of learning media that is less than optimal; and various other problems. Therefore, in this study, we will raise a problem with the title "Problematics of the Implementation of Thematic Learning at SDN Cluster 7 Pujut District for the 2019/2020 Academic Year". The objectives of this study are: to determine the process of implementing learning; problems experienced by teachers and students; and how to overcome problems experienced by teachers and students during learning. Data collection methods used are observation, interviews, and documentation. This research was carried out at SDN cluster 7, Pujut District for 1 (one) month, from October to November 2019. The results of this study are: The problems experienced by teachers are: teachers are less creative in choosing learning media; less than optimal class conditions; the use of learning methods is less varied; and inadequate facilities and infrastructure. Meanwhile, the problems experienced by students are: the slow reading and writing ability of students; students are less active and enthusiastic in the learning process; and low student attendance at school. One of the solutions to overcome these problems is that teachers must be creative in choosing learning media. The suggestion that the author proposes is that teachers must always apply interesting learning methods in carrying out the learning process so that students are enthusiastic and serious in following the implementation of the learning that has been planned.